Quality Ready to wear fashion with QR Code Technology Innovation Using the Mandala Batik Technique Modification - Della Nurfadhilah; Irmayanti Irmayanti (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
The development of digital technology encourages innovation in the fashion industry, especially in ready-to-wear clothing, which involves not only aesthetic aspects but also functional values. This study aims to examine the quality of ready-to-wear clothing incorporating QR Code technology and contemporary batik with the Teknika Mandala motif. The Research method used is the method of creation of works with a design approach, which includes the stages of exploration, design, and embodiment. The resulting clothing products are then tested for quality using descriptive percentages based on assessments from expert panelists and trained panelists. The assessment indicators for product quality include design, size, aesthetics, sewing techniques, clothing performance, and product features. The results show that ready-to-wear clothing with QR Code technology innovation and Teknika Mandala batik modifications obtained an average score of 85% and is included in the very decent category. The sewing technique and product features received the highest scores, while the size aspect received the lowest score, although it is still in the decent category. These results indicate that applying QR Code technology to contemporary batik-based ready-to-wear clothing can improve product quality and provide functional and innovative value relevant to the development of digital technology.